EFFECT OF INCORPORATION OF FYM, PIGEONPEA STALK, PHOSPHOCOMPOST ON GROWTH, YIELD AND NUTRIENT UPTAKE IN PIGEONPEA BASED INTERCROPPING SYSTEM - NAGAR, R. K; KUMAR, RAVINDRA; GOUD, V. V (The Bioscan, 2015)
A field experiment was conducted to study the response of organic manure (FYM) and crop residue (Pigeonpea stalk) on pigeonpea intercropped with greengram and blackgram (1:2) on Inceptisolat Pulses Research Unit, Dr. Panjabrao Deshmukh Krishi Vidyapeeth, Akola (Maharashtra) during kharif season of 2013-14. Among different cropping system Pigeonpea + blackgram intercropping system recorded maximum number of branches (16.31), dry matter accumulation (97.53 g), number of pods plant-1 (106.7), test weight (8.49 g), grain weight plant-1 (33.88 g), pigeonpea equivalent yield(2002 kg ha-1)and harvest index (26.1 %)while highest plant height (175.3 cm), seed yield, straw yield, biological yield(1601, 5146, 6710 kg ha-1 respectively) and N, P, K, uptake( 92.5, 9.6, 58.4 kg ha-1 respectively) were recorded in sole pigeonpea. In case of total nutrient uptake highest uptake of [N and P(105.8, 19.3 kg ha-1) respectively] was recorded with Pigeonpea+ blackgram intercropping system over remaining intercropping system, however, uptake of potassium was more with (58.4kg ha-1) sole pigeonpea. Among nutrient management application of inorganic fertilizer (25:50 kg N:P2O5 ha-1) and organic manures in combination with phosphocompost recorded statistically equivalent growth and yield attributes andNPK uptake.